(3UMGaI GdedMb h JWhQ GdUMGaI GdYQHjI (B:s (3GSJOQGc (B/s - (3NVQ, SYO GdOjfs ([(3Ohf ecGf(B] :s (3OGQ GdcJGH ddWHGYI h GdfTQ ,s)
(3JJfGhd gPg GdOQGSI GdQjYI ehVhY JWhQ GdUMGaI GdYQHjI (B((3GUOGQ GdedGMb(B) (3NdGd GdYbhO GdKdGKI GdGNjQI GdefUQeI ef gPG GdbQf h MJi fgGjI YGe (B1971 (3h eG UOQ HYO gPG GdYGe dG jONd aj SjGb HMKfGs
Keywords: (3GdUMGaIs; (3GdUMGaI GdYQHjIs